Perceptions of Not Getting Married Among Generation Z Through TikTok - Ropiah Ropiah; Siti Khumayah; Aghnia Dian Lestari (Universitas Medan Area, 2026)
Shifting attitudes toward marriage have become increasingly evident among Generation Z in Indonesia as TikTok has emerged as a prominent platform where narratives surrounding remaining unmarried, singlehood, and childfree lifestyles are widely circulated and negotiated. While previous studies have primarily examined the relationship between social media exposure and changing attitudes toward marriage, limited attention has been given to how digital social construction processes shape these perceptions. This study aims to analyze the representation of unmarried narratives on TikTok, examine how these narratives are socially constructed through digital interactions, and identify the factors influencing Generation Z's perceptions of remaining unmarried. Employing a descriptive qualitative approach, the study collected data through in-depth interviews with six Generation Z participants aged 20–27, observations of five TikTok accounts, and document analysis. The findings reveal five dominant narrative framings on TikTok-risk, responsibility, self-worth, statistical legitimacy, and anti-timeline-which interact with users through the processes of externalization, objectification, and internalization as conceptualized by Berger and Luckmann. Most participants reported shifts in their perceptions after repeated exposure to these narratives, although the extent of change varied according to their personal values, family backgrounds, and life experiences. Rather than claiming a deterministic influence of TikTok, this study demonstrates that digital platforms function as spaces where social meanings about marriage are continuously negotiated and reconstructed. The study contributes to the literature on digital social construction by illustrating how algorithmically mediated interactions participate in reshaping contemporary marriage values among Generation Z in Indonesia while highlighting the importance of critical digital literacy and intergenerational communication in responding to evolving digital narratives.